Association of Circulating Metabolites in Plasma or Serum and Risk of Stroke: Meta-analysis From 7 Prospective Cohorts. (23rd February 2021) - Vojinovic, Dina; Kalaoja, Marita; Trompet, Stella; Fischer, Krista; Shipley, Martin J.; Li, Shuo; Havulinna, Aki S.; Perola, Markus; Salomaa, Veikko; Yang, Qiong; Sattar, Naveed; Jousilahti, Pekka; et al.
Abstract : Objective: To conduct a comprehensive analysis of circulating metabolites and incident stroke in large prospective population-based settings. Methods: We investigated the association of metabolites with risk of stroke in 7 prospective cohort studies including 1, 791 incident stroke events among 38, 797 participants in whom circulating metabolites were measured by nuclear magnetic resonance technology. The relationship between metabolites and stroke was assessed with Cox proportional hazards regression models. The analyses were performed considering all incident stroke events and ischemic and hemorrhagic events separately. Results: The analyses revealed 10 significant metabolite associations. Amino acid histidine (hazard ratio [HR] per SD 0.90, 95% confidence interval [CI] 0.85, 0.94; p = 4.45 × 10 −5 ), glycolysis-related metabolite pyruvate (HR per SD 1.09, 95% CI 1.04, 1.14; p = 7.45 × 10 −4 ), acute-phase reaction marker glycoprotein acetyls (HR per SD 1.09, 95% CI 1.03, 1.15; p = 1.27 × 10 −3 ), cholesterol in high-density lipoprotein (HDL) 2, and several other lipoprotein particles were associated with risk of stroke. When focused on incident ischemic stroke, a significant association was observed with phenylalanine (HR per SD 1.12, 95% CI 1.05, 1.19; p = 4.13 × 10 −4 ) and total and free cholesterol in large HDL particles. Conclusions: We found association of amino acids, glycolysis-related metabolites, acute-phase reaction markers, and several lipoprotein subfractions with the risk of stroke. These findings support the potential of metabolomics to provide new insights into the metabolic changes preceding stroke.